Assessing the in vitro cytotoxicity of synthesized chitosan nanoparticles against different organic and inorganic nanomaterials in human kidney cancer cells - Faudzi, Hanis (2015)
One of the biggest concerns regarding the use of nanomaterials for biological and medical applications is its toxicity. A simple way to evaluate nanomaterials’ toxicity is by conducting in vitro cytoxicity assays. In this study, the synthesis of chitosan nanoparticles (CNP) and the colorimetric MTT assay of CNP along with various organic and inorganic nanomaterials were explored. CNP were synthesised via ionic gelation routes and particle size distribution were analysed using dynamic light scattering (DLS) supplemented with field-emission scanning electron microscopy (FE-SEM) imaging. The 786-O human kidney cancer cell lines were established and treated with various concentrations of CNP, carbon nanotubes (CNT), layered double hydroxides (LDH), solid lipid nanoparticles (SLN), and iron oxide nanoparticles for MTT assay. The morphologies of cells treated with each nanomaterial were also observed. DLS analysis showed that nanoparticles with average size of 67.70 nm were obtained using a formulation of 600 μl of 0.5 mg/ml chitosan solution and 250 μl of 0.7 mg/ml tripolyphosphate (TPP) solution (CNP-F3) and was further supported by FE- SEM results. Results from MTT assay showed that cells treated with 1 mg/ml SLN and CNP-F3 gave the highest cell viability of 49.38% and 39.72%, respectively. Cells treated with 1 mg/ml CNT gave the lowest cell viability of 31.54%. These results were consistent with the observations made on cell morphologies, implying that both organic CNP and SLN were the least toxic. The inorganic nanomaterials tend to be more toxic, with CNT being the most toxic.